Pengembangan Perangkat Pembelajaran Matematika Menggunakan Model Problem Based Learning Untuk Memfasilitasi Kemampuan Representasi Matematis Peserta Didik - Ovemy Delfita; Nahor Murani Hutapea; Atma Murni (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2020)
The ability of mathematical representation is an ability that students should have in order to assist in interpreting problems into verbal, visual, and symbolic forms. The low ability of students' mathematical representation and learning tools that are made by the teacher has not facilitated enough the ability of mathematical representation the main objective of this study. Researchers developed learning tools consisting of syllabus, lesson plans, and student worksheet using the Problem Based Learning model to improve students' mathematical representation skills. The development model used is the Borg and Gall’s model. The instruments used were validation sheets and student response questionnaires. The data analysis technique used is the analysis of validity and practicality. The result of the percentage of validity shows that the learning device is included in the valid category with an average syllabus percentage of 92.18%, RPP is 93.64% and LKPD is 93.06%. The student response questionnaire analysis showed that the device was included in the very practical category with an average of 92.2%. The tools developed by researchers have met the valid and practical categories to facilitate the mathematical representation abilities of students.